Construction of a Fundamental Solution of a Perturbed Parabolic Equation - Bondarenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We propose a method for the construction of a solution of a parabolic equation in the case where the diffusion operator is perturbed.